Solve for y y^2-2y-24y=0

Math
y2-2y-24y=0
Subtract 24y from -2y.
y2-26y=0
Factor y out of y2-26y.
Tap for more steps…
Factor y out of y2.
y⋅y-26y=0
Factor y out of -26y.
y⋅y+y⋅-26=0
Factor y out of y⋅y+y⋅-26.
y(y-26)=0
y(y-26)=0
If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
y=0
y-26=0
Set the first factor equal to 0.
y=0
Set the next factor equal to 0 and solve.
Tap for more steps…
Set the next factor equal to 0.
y-26=0
Add 26 to both sides of the equation.
y=26
y=26
The final solution is all the values that make y(y-26)=0 true.
y=0,26
Solve for y y^2-2y-24y=0

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top